Estrategias de sustentabilidad del Restobar La Bacana de la ciudad de Babahoyo - Aguirre Ycaza, Julio César (2021)
This case study called: Sustainability Strategy of the Restobar "La Bacana" in the city of Babahoyo, analyzes the shortcomings and difficulties of the undertakings after the arrival of the pandemic in the country, through a unit of analysis such as the aforementioned institution, to understand the difficulties of small businesses today, in order to describe the problems that can be improved in the internal administration of the organization. Through a descriptive-bibliographic research methodology together with the implementation of technical instruments for the correct collection of information such as the survey and interview applied to the owner manager and consumers of the premises, each of the inconveniences found in the target institution will be described. study with its particularities based on previously defined theoretical support in order to successfully conclude the deductive method applied by the current document on the sustainability of the Restobar "La Bacana", which as a result of the research showed that the restobar satisfies the customer with the quality of their product, however, the attention is not adequate from the employees as mentioned by the owner manager.